Effect of Phosphorus and Potassium Fertilizers Application on Soil Chemical Characteristics and Their Accumulation in Potato Plant Tissues. (15th December 2022) - Setu, Habtam
Abstract : Applications of nutrients are determined by the plant's nutritional requirements and the soil's available nutrients; however, the precise nutrient application is difficult. At Assosa, a field experiment was conducted to determine how soil chemical characteristics and accumulation of phosphorus and potassium in potato tissue responded to phosphorus and potassium fertilizers application. The treatments included four potassium levels (0, 100, 200, and 300 kg·K2 O ha −1 ) and six phosphorus levels (0, 46, 92, 138, 184, and 230 kg·P2 O5 ha −1 ). The experiment was set up as a factorial randomized complete block design (RCBD) and was repeated three times. According to the preplanting soil analysis, the cropping area's soil has a medium CEC, low accessible phosphorus, and very low exchangeable potassium. The application of phosphorus had a highly significant influence on accessible phosphorus, exchangeable potassium, and CEC, the concentration of phosphorus in the leaf and tuber tissue of the potato plant. While potassium had a significant effect on exchangeable potassium, CEC, phosphorus concentration in potato plant tuber tissue, and potassium level in both the leaf and the tuber, the interaction effect of phosphorus and potassium on all of the above-mentioned soil chemical properties, as well as the amount of P and K in potato plant tissues, was observed. The critical potassium level in the leaf blade for optimum crop yield tissue content was determined to be 100 kg·K2 O ha −1, while the critical level of phosphorus was determined to be 184 kg·P2 O5 ha −1 .